Molecular Identification of Shark Meat From Local Markets in Southern Brazil Based on DNA Barcoding: Evidence for Mislabeling and Trade of Endangered Species - Almerón-Souza, Fernanda; Sperb, Christian; Castilho, Carolina L.; Figueiredo, Pedro I. C. C.; Gonçalves, Leonardo T.; Machado, Rodrigo; Oliveira, Larissa R.; Valiati, Victor H.; Fagundes, Nelson J. R. (Frontiers in Genetics, 2018)
Elasmobranchs, the group of cartilaginous fishes that include sharks and rays, are especially vulnerable to overfishing due to low fecundity and late sexual maturation. A significant number of elasmobranch species are currently overexploited or threatened by fisheries activities. Additionally, several recent reports have indicated that there has been a reduction in regional elasmobranch population sizes. Brazil is an important player in elasmobranch fisheries and one of the largest importers of shark meat. However, carcasses entering the shark meat market have usually had their fins and head removed, which poses a challenge to reliable species identification based on the morphology of captured individuals. This is further complicated by the fact that the internal Brazilian market trades several different elasmobranch species under a common popular name: “cação”. The use of such imprecise nomenclature, even among governmental agencies, is problematic for both controlling the negative effects of shark consumption and informing the consumer about the origins of the product. In this study, we used DNA barcoding (mtDNA, COI gene) to identify, at the species level, "cação" samples available in local markets from Southern Brazil. We collected 63 samples traded as “cação”, which we found to correspond to 20 different species. These included two teleost species: Xiphias gladius (n=1) and Genidens barbus (n=6), and 18 species from seven elasmobranch orders (Carcharhiniformes, n=42; Squaliformes, n=3; Squatiniformes, n=2; Rhinopristiformes, n=4; Myliobatiformes, n=3; Rajiformes, n=1; and Torpediniformes, n=1). The most common species in our sample were Prionace glauca (n=15) and Sphyrna lewini (n=14), while all other species were represented by four samples or less. Considering IUCN criteria, 47% of the elasmobranch species found are threatened at the global level, while 53% are threatened and 47% are critically endangered in Brazil. These results underline that labelling the meat of any shark species as “cação” is problematic for monitoring catch allocations from the fishing industry and discourages consumer engagement in conservationist practices through informed decision-making.